(untitled) (Research, Society and Development, 2020)
Saprolegniosis is a mycological disease that causes significant economic losses in fish culture and can be considered an obstacle to the development of world fish farming. Thus, we aimed to identify which species of fish cultivated in the world have been associated with fungi of the genus Saprolegnia. The research deals with a bibliographical survey that contemplates articles published between 2007 and July of 2017. We found a relationship of saprolegniose with fish species: Oncorhynchus mykiss, Salmo trutta, Oncorhynchus tshawytscha, Labeo rohita, Pterophyllum scalare, Ctenopharyngodon idella, Sander lucioperca, Pelteobagrus fulvidraco, Oreochromis niloticus, Odonthestes bonariensis, Odonthestes humensi e Catla catla. The oomycetes found were: Saprolegnia ferax, Saprolegnia parasitica, Saprolegnia australis, Saprolegnia diclina, Saprolegnia delica, Saprolegnia glomerata, Saprolegnia terrestres, Saprolegnia uliginosa, Saprolegnia unispora, Saprolegnia hypogyna and Saprolegnia longicaulis. The species S. ferax and S. parasitica were the fungi that presented the highest infection register, mainly in salmonids. O. mykiss, S. salar and S. trout were the fish with more studies related to saprolegniose, because they are species that have great market importance in the world fish farming scenario. Despite the great importance of the species O. niloticus in the world fish culture, we observed the specie in only one article in this research, which may be related to the high resistance of the species to diseases and to the lack of research funding to identify this type of infection. It was not possible to compare the host - etiological agent among the fish, since many of the studies considered in the research did not have the purpose of identifying the pathogen.